2001
DOI: 10.1103/physrevlett.87.248101
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Map Formation in the Barn Owl’s Brain

Abstract: Barn owls provide an experimentally well-specified example of a temporal map, a neuronal representation of the outside world in the brain by means of time. Their laminar nucleus exhibits a place code of interaural time differences, a cue which is used to determine the azimuthal location of a sound stimulus, e.g., prey. We analyze a model of synaptic plasticity that explains the formation of such a representation in the young bird and show how in a large parameter regime a combination of local and nonlocal syna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Such an STDP mechanism has been demonstrated in many preparations (25,26), in particular in the auditory system (27). It has been shown that STDP can account for the development of ITD-sensitive neurons (28)(29)(30). However, these studies addressed only the learning of temporal delays.…”
Section: Resultsmentioning
confidence: 97%
“…Such an STDP mechanism has been demonstrated in many preparations (25,26), in particular in the auditory system (27). It has been shown that STDP can account for the development of ITD-sensitive neurons (28)(29)(30). However, these studies addressed only the learning of temporal delays.…”
Section: Resultsmentioning
confidence: 97%
“…Synaptophysin and syntaxin immunoreactivity also increase in NM and NL between E12 and E16 (Alladi et al., 2002). Modeling studies in the barn owl have proposed that formation of a computational map for interaural time differences in NL is mediated by the action of homosynaptic spike-based Hebbian learning Leibold et al, 2001). NR2A and NR2B subunits are of central importance in models of Hebbian learning and memory (Lisman et al, 2002;Liu et al, 2004;Massey et al, 2004), and we propose that early expression of NR2B contributes to synapse formation in the circuit for detection of interaural time differences.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Since this adaptation is frequency-specific, it must occur at an early stage in the auditory pathway: it has indeed been identified in the lateral shell and external nucleus of the inferior colliculus Knudsen, 1999, 2000). Previous modeling studies have also shown that STDP is a viable mechanism for the development of ITD selectivity (Gerstner et al, 1996;Kempter et al, 2001;Leibold et al, 2001;Leibold and van Hemmen, 2005). Thus, these two assumptions are plausible and are sufficient to account for the frequency dependence of BDs.…”
Section: Discussionmentioning
confidence: 91%
“…This mechanism has been demonstrated in vitro in many preparations (Markram et al, 1997;Poo, 1998, 2001;Caporale and Dan, 2008), in particular in the auditory system (Tzounopoulos et al, 2004), and has been the subject of many modeling studies (Kempter et al, 1999;Song et al, 2000;van Rossum et al, 2000), including in the context of ITD selectivity (Gerstner et al, 1996;Kempter et al, 2001;Leibold et al, 2001;Leibold and van Hemmen, 2005). Specifically, we consider a plasticity rule where synaptic modification is determined by the difference in timing of postsynaptic and presynaptic spikes, at each synapse (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation